(3SbW GdLhGgQ GdCOHjI aj GdZQjH ef CdaGX GddZI GdYQHjIs - (3GHf CHj YeQ GdUfYGfjs
(3ChdgG (B:s
(3eJHGjfI GdJQJjH , aefgG eGgh eJYQ Yf GdVHW , hefgG eGgh eMQhS HGdMQcGJ Ohf GdfbW hMQUJ Gf jLeY efgG cJGH jTJed Ydi UQjM CdaGX GddZI GdCUdjI hLYdJ JQJjH cJGHi gPG Ydi JQJjH VjGA GdMdbhe ZjQ Cfi CPcQgG gfG HJQJjH GdMQha hGdChRGf s
(3BNQgG (B:s
(3HGH GdTjf hGdhGh heG HYOgeG , GdCSeGA (B: (3aYd HaJM GdaGA hSchf GdYjf , bhdg a (B: (3GdTha GdLGA , hTja eTha , hOjfGQ eTha Ci eLdh s
(3GdNW eged GdfbW CMjGfkGs
(3hYdi MhGTjgG ebGHdGJs
(3cJHJ GdYfhGfGJ HGdMeQIHgG JbWjYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs